Justice scolaire pour les hérissons : la prise en compte de la parole des élèves au sein des conseils de discipline - Vincent Lorius (Recherches en Éducation)
This text is based on research on the functioning of disciplinary councils in a department of metropolitan France. These bodies are in fact particularly instructive to learn about the way in which the voices of children and adolescents are taken into account within the education system. In the first part, we will indicate why hearing the pupils’ words to be concerned effectively with the real effects produced by the educational supports and not only with the coherence of the principles which are supposed to guide them. Regarding children’s speech, this vigilance must make it possible to verify that the recurrent announcement to allow the expression of students does not contradict the effects of educational practices.) By means of some results, we will show that this risk is very real within the disciplinary bodies and we will try to update some explanatory reasons for this situation, the common characteristic of which is to raise moral questions. Among these is an excessive use of a common sense school ethic which makes respect for values the whole of education.